Malaysian rail supporting industry roadmap 2030 - Kamarulzaman Zainal; Mohd Nasir Md Ibrahim, editor; Bisop, Priscilla Annabel, editor; Rushdi Abdul Rahman, editor; Mohd Nurul Azammi, editor; Mohd Afzanizam Mohd Badrin, editor; Malaysia. Malaysian Industry-Government Group for High Technology (MIGHT) (Selangor : Malaysian Industry-Government Group for High Technology, 2014)
Includes directory